Personality and Psychoneuroimmunology: Patient Perspectives on Mind-Body Health - Lee, Angel; Wong, Yoko; Neo, Xian Seng (Journal of Personality and Psychosomatic Research (JPPR), 2024)
This study aimed to explore patient perspectives on the relationship between personality and psychoneuroimmunology (PNI) with a focus on mind-body health, providing insights into how psychological states and personality traits influence physical health outcomes. A qualitative research design was employed, utilizing semi-structured interviews with 20 participants recruited from various healthcare settings. The interviews were conducted until theoretical saturation was reached. Data were analyzed using thematic analysis with the aid of NVivo software to identify key themes and subthemes related to the mind-body connection, the impact of stress, personality traits, and coping mechanisms. Participants reported a strong belief in the holistic nature of health, with thoughts and emotions significantly influencing their physical health. Key themes identified include the influence of emotions (mentioned by 80% of participants), psychosomatic symptoms (65%), stress triggers (70%), and the role of social support (75%). Personality traits such as optimism and resilience were linked to better health outcomes (60%), while negative traits like hostility exacerbated health issues (55%). Mindfulness and coping strategies were reported as effective in managing health (70%). The study highlights the intricate interplay between psychological factors, personality traits, and physical health. Patients perceive a significant connection between their mental and physical states, emphasizing the need for holistic healthcare approaches that integrate psychological support with traditional medical treatments. The findings align with existing PNI research, underscoring the importance of addressing emotional well-being and personality traits in healthcare.